2016
DOI: 10.1177/1758834016639873
|View full text |Cite
|
Sign up to set email alerts
|

Targeted chemotherapy with nanoparticle albumin-bound paclitaxel (nab-paclitaxel) in metastatic breast cancer: which benefit for which patients?

Abstract: Abstract:The therapeutic goals in metastatic breast cancer (MBC) remain palliative in nature, aimed at controlling symptoms, improving or maintaining quality of life and prolonging survival. The advent of new drugs and new formulations of standard agents has led to better outcomes in patients with advanced or metastatic disease. These developments have also allowed a tailored therapeutic approach, in which the molecular biology of the tumour, the treatment history, and patient attitudes are taken into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 97 publications
1
18
0
2
Order By: Relevance
“…This result is in agreement with the published data showing a greater risk of mild–moderate side effects associated with nab-paclitaxel treatment. In our study, we also found a significant impact of nab-paclitaxel on pain reduction and this was linked to better survival and improvement of QoL 29. We realize, however, that despite our results being in line with those reported in the literature, there are limits that must be taken into consideration, related for example, to the evaluation of the response and to the small size of the sample.…”
Section: Discussionsupporting
confidence: 83%
“…This result is in agreement with the published data showing a greater risk of mild–moderate side effects associated with nab-paclitaxel treatment. In our study, we also found a significant impact of nab-paclitaxel on pain reduction and this was linked to better survival and improvement of QoL 29. We realize, however, that despite our results being in line with those reported in the literature, there are limits that must be taken into consideration, related for example, to the evaluation of the response and to the small size of the sample.…”
Section: Discussionsupporting
confidence: 83%
“…[2][3][4][5][6][7] Furthermore, other widely used drugs in this setting are vinorelbine, gemcitabine, ixabepilone (not approved by European Medicines Agency), nab-paclitaxel (where available) and liposomal anthracyclines. [8][9][10][11][12] Eribulin mesylate is an irreversible, non-taxane, microtubule growth inhibitor with a novel mechanism of action, also capable to overcome taxane resistance. 13 14 On the basis of the results of phase III trials, study 305 (EMBRACE) in which median overall survival (OS) was significantly longer with eribulin compared with the treatment of physician's choice (13.1 vs 10.6 months, p=0.041) and study 301, and the pooled analysis of both aforementioned trials, 7 15 16 eribulin was approved in the USA (November 2010) and in Europe (March 2011) for the treatment of MBC previously treated with at least two lines of chemotherapy, including anthracyclines and taxanes, and with at least one chemotherapy regimen, respectively.…”
Section: Key Questionsmentioning
confidence: 99%
“…Numerous therapeutic drugs are delivered by HSA [31]. For example, the albumin paclitaxel (PTX) nanoparticle (Abraxane ® ) has already been approved by the FDA for the treatment of metastatic breast cancer [32, 33]. However, a major drawback of the conventional method for Abraxane ® preparation is the need for toxic chlorinated organic solvents [34].…”
Section: Introductionmentioning
confidence: 99%